VISTA expression associated with CD8 confers a favorable immune microenvironment and better overall survival in hepatocellular carcinoma - Zhang, Ming (BMC Cancer, 2018)
BACKGROUND: Hepatocellular carcinoma (HCC) often arises in the setting of chronic inflammation with multiple inhibitory immune signals. V-domain Ig suppressor of T cell activation (VISTA) is identified as a novel negative checkpoint regulator. This study sought to determine the expression and prognostic value of VISTA in HCC and classify tumor microenvironments (TMEs) based on VISTA and CD8+ tumor-infiltrating lymphocytes (TILs). METHODS: The expression of VISTA and CD8 proteins was assessed in 183 HCC tissue microarrays (TMAs) by immunohistochemistry (IHC). VISTA and CD8A mRNA extracted from 372 patients with HCC in The Cancer Genome Atlas (TCGA) database was included as a validation cohort. Associations between the VISTA, clinicopathological variables, and survival were analyzed. RESULTS: VISTA expression was detected in 29.5% HCC tissues, among which 16.4% tissues were positive for tumor cells (TCs), and 16.9% tissues were positive for immune cells (ICs). VISTA expression was significantly associated with tissues with a high pathological grading (p = 0.038), without liver cirrhosis (p = 0.011), and with a high density of CD8 + TILs (p < 0.001). Kaplan-Meier curves demonstrated that patients with VISTA-positive staining in TCs (p = 0.037), but not in ICs, (p = 0.779) showed significantly prolonged overall survival (OS) than those with VISTA-negative expression. Classification of HCC TME-based VISTA and CD8 + TILs showed 4 immune subtypes: VISTA+/CD8+ (16.9%), VISTA+/CD8- (12.6%), VISTA-/CD8+ (16.4%), and VISTA-/CD8+ (54.1%). The dual positive VISTA+/CD8+ subtype showed significantly prolonged OS than other subtypes (p = 0.023). CONCLUSIONS: VISTA protein expression in HCC showed cell specific and displayed different prognosis. VISTA expression was significantly associated with CD8 + TILs, Dual positive VISTA+/CD8+ showed favorable TME and better OS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4435-1) contains supplementary material, which is available to authorized users.